Steatocystoma multiplex as initial impression of non-small cell lung cancer with complete response to gefitinib - Tsai, Ming-Hung; Hsiao, Yu-Ping; Lin, Wea-Lung; Tseng, Szu-Wen (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Cutaneous metastases are rare and seldom present at the time of first diagnosis of cancer. Data from various studies show that 1-12% of lung cancer patients experience tumor spread to the skin. The scalp, chest, and abdomen are favored sites of skin metastases from lung cancers, but metastases to multiple skin sites in a single patient are rarely reported. We describe a 56-year-old lung adenocarcinoma patient, initially diagnosed with steatocystoma multiplex who responded well to gefitinib treatment. The efficacy of conventional chemotherapy for cutaneous metastases has been limited because of the relatively poor blood supply to the skin. It has been demonstrated that tyrosine kinase inhibitor (TKI), gefitinib, has significant clinical benefit in lung cancer patients with epidermal growth factor receptor (EGFR) mutation even in metastases to the brain. However, the therapeutic response to gefitinib in patients with skin metastases is seldom mentioned in the literature. We report one case of lung adenocarcinoma with multiple skin metastases that were successfully treated with gefitinib.